A Scoping Review of Idiographic Research in Education: Too Little, But Not Too Late - Ito, Hibiki; Lopez-Pernas, Sonsoles; Saqr, Mohammed (Proceedings (IEEE International Conference on Advanced Learning Technologies), 2024)
It stands to reason that if we want to offer "personalized" education, our methods should be designed to capture the person and the intraindividual processes. However, an idiographic approach that investigates within-person processes and provides insights on the person has been so far lagging. We conducted a scoping review to explore how the idiographic approach has been applied in educational research (i.e., what methods, topics, data, and statistical approaches). We found that person-specific analysis has mostly been used to investigate education psychology constructs. In addition,Except for a few exceptions in learning analytics, many idiographic studies have employed basic statistical techniques, whereas advanced statistical methods have been applied only recently. Therefore, considering the recent development of educational data science, the potential of idiographic methodology needs to be explored further.